Articulating Institutions and Communities for Integral Security; [Articulando Instituições E Comunidades Para a Segurança Integral] - Cifuentes-Contador, S (Universidad Nacional de Colombia, 2023)
The objective of this article is to analyze the neighborhood insecurity and security, from the perspective of neighbors, community leaders and key actors of a social intervention done in a vulnerable territory of Santiago, Chile. Qualitative methodology was used, eleven interviews were conducted, and five focus groups were created, in which 46 people participated. Institutional and community articulation for integral security is the main result. The sensation of insecurity is described, associated to the external , which produces learned hopelessness, isolation and confinement inside homes, as well as low neighborhood participation. In contrast, the sensation of security is presented, associated with the internal , with the strategies of self-defense and personal and community strengthening. The effects of these strategies are reported, focusing on information and group reflection on issues relevant to security, the strengthening of neighborhood relations, and the care and appropriation of public spaces. The scope of the intervention is recognized in relation to increasing the feeling of security and its limitation in terms of decreasing the feeling of insecurity; and recommendations to move towards integral security are offered. © 2023 Universidad Nacional de Colombia. All rights reserved.